Enhancing Students Listening Comprehension through Picture Dictation (Classroom Action Research) - Kusdiantini, Anisah Diniati (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This Classroom Action Research study aimed to investigate the effectiveness of enhancing students' listening comprehension through picture dictation in the 8th G class of SMPN 2 Kota Sorong, with a sample size of 27 students. The research instrument included pre-test and post-test listening comprehension assessments, supplemented by visual stimuli to evaluate students' ability to understand spoken language and make inferences. A survey was administered to gather students' feedback on their engagement with picture dictation activities. The data analysis involved comparing pre-test and post-test scores, utilizing statistical tests to assess improvements in listening skills. The data indicates that the students' average score on the pretest or diagnostic test was 61.56. During the posttest 1 of the cycle, the mean score was 73.97. After administering treatment in the second cycle, the average score increased to 84.31. It showed that the use of picture dictation enhanced the students' listening comprehension. The results indicated a significant enhancement in students' listening comprehension following the implementation of picture dictation activities. The study's findings suggest that integrating visual aids in listening tasks can effectively support students' comprehension skills and promote active learning in the classroom setting.